DEVELOPMENT OF MAGNETIC ROULETTE MEDIA BY USING DISCOVERY LEARNING FOR THE INTRODUCTION OF SYMBOLS 1-10 IN CHILDREN AGED 4 - 5 YEARS AT HIDAYATUS SHIBYAN KINDERGARTEN SURABAYA - Nurkayatin, Widya; Hasibuan, Rachma; Khotimah, Nurul (Universitas Islam Negeri (UIN) Sumatera Utara, 2025)
This study aims to produce a product in the form of a magnetic roulette learning media that is developed and tested for its feasibility using validity and product trials, in order to determine the extent to which the level of achievement of the development of the ability to recognize the concept of number symbols 1-10 in children aged 4-5 years at Hidayatus Shibyan Kindergarten Surabaya after teaching and learning activities with magnetic roulette learning media using the Discovery Learning learning model. The research design used in this study is a type of development research with a 4D research model (Four D- Models). This 4D development model consists of 4 stages of namely define, design, develop and disseminate. The results of the study on the effectiveness of the “Roulette Magnet” learning media, proven by the calculation of N-Gain, which shows an overall increase in pre-test and post-test scores of 0.597 in moderate interpretation. These results indicate that the “Roulette Magnet” learning media can improve the quality of learning and support learning objectives, so that the “Roulette Magnet” learning media in the teaching material for introducing the concept of numbers 1-10 in children aged 4-5 years is declared effective. The conclusion based on all the results of the analysis and assessment of experts and education practitioners, both teachers and students, is that the “Roulette Magnet” learning media is classified as a media that is suitable for use in the learning process.